2018
DOI: 10.21621/sajms.2018122.04
|View full text |Cite
|
Sign up to set email alerts
|

Shari’ah Governance and Islamic Banks Performance: Evidence from South Asia

Abstract: Shari'ah governance provide strike conformity with Islamic businesses ethics and the expectation of its customers which aim at improving firms performance and societal welfare to eliminate poverty in the global setting. The purpose of this study is to investigate the impact of Shari'ah governance on Islamic banks (IBs) performance of 31 IBs of 4 countries of South Asia for the period of 2010-2016 and developed a CG index for IBs. Two types of analysis were performed; descriptive statistics and panel random eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Empirically, measuring financial performance of Islamic banks can use the proxies of earning ability or profitability, which has been conducted by Buallay (2019), Ajili and Bouri (2018), Farag et al (2018), Hakimi et al (2018), Khan et al (2018), Nomran et al (2018), Almutairi and Quttainah (2017), Mollah and Zaman (2015), and Matoussi and Grassa (2012).…”
Section: Background Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Empirically, measuring financial performance of Islamic banks can use the proxies of earning ability or profitability, which has been conducted by Buallay (2019), Ajili and Bouri (2018), Farag et al (2018), Hakimi et al (2018), Khan et al (2018), Nomran et al (2018), Almutairi and Quttainah (2017), Mollah and Zaman (2015), and Matoussi and Grassa (2012).…”
Section: Background Of the Studymentioning
confidence: 99%
“…SSB expertise can consist of accounting, economics, business and law (Ginena & Hamid, 2015;Hassan et al, 2010). SSB is demanded not only for its sharia education, but also for expertise because banks are complex business entities (Ginena & Hamid, 2015;Khan et al, 2018). If SSB members have these qualifications of expertise, it will increase the effectiveness of SSB's duties, responsibilities and functions.…”
Section: Ssb Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…Second, considering Islamic banks’ limited level of tax avoidance literacy, they do not understand the underlying principles of tax avoidance. Put simply, empirical research on Islamic banks typically focuses on linking SSB characteristics with financial performance, as evidenced by Abdallah and Bahloul (2021), Buallay (2019), Ajili and Bouri (2018), Farag et al (2018), Hakimi et al (2018), Khan et al (2018), Almutairi and Quttainah (2017), Nomran et al (2018), Nomran et al (2017), Mollah and Zaman (2015) and Matoussi and Grassa (2012) or linking SSB characteristics with compliance with prevailing Shari’ah laws, as evidenced by Muhammad et al (2021) and Alam et al (2021); however, it has been difficult to identify SSB characteristics literacy that has the potential to reduce tax avoidance practices.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of Basiruddin and Ahmed (2019) showed that the Shariah committee reduced the Shariah non-compliant risk. Meanwhile, Khan, Zahid, and Akhtar (2018) has concluded that larger Shari'ah boards, which is similar to Shariah committees in Malaysia, can enhance the value of the Islamic banks. The reason is that such board members have various ethical and religious backgrounds; combining their educational credentials and professional experience, which larger size will assist the board of directors in addressing Shariah-compliant activities in the banks.…”
Section: Shariah Committeementioning
confidence: 99%